The Effect of Business Risk, Firm Size, and Debt Policy on Financial Performance: Evidence from Technology Sector Companies Listed on the Indonesia Stock Exchange - Boniza Febriana Putra Pratama; Sri Anjarwati (SEAN Institute, 2026)
This study aims to analyze the effect of business risk, firm size, and debt policy on the financial performance of technology-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research applies a quantitative approach using panel data regression analysis based on secondary data obtained from the financial statements of technology companies listed on the IDX. Financial performance is measured by Return on Equity (ROE), while the independent variables consist of business risk, firm size, and debt policy, with debt policy proxied by the Debt to Equity Ratio (DER). The findings indicate that business risk, firm size, and debt policy have different effects on financial performance during the observation period. These results are expected to provide useful insights for company management in improving financial performance through effective business risk management, appropriate company scale, and prudent debt policies. The study also provides practical considerations for investors and policymakers in evaluating financial strategies in the technology sector. The originality of this research lies in its focus on Indonesian technology companies during the post-pandemic period and in the simultaneous examination of business risk, firm size, and debt policy as determinants of financial performance.